Respostas
respondido por:
2
an = a1 + (n-1) . r
an = -3 + (15-1) . 7
an = -3 + 14 . 7
an = -3 + 98
an = 95
||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||
s = (a1 + an) . n
----------------------
2
s = (-3 + 95) . 15
-------------------------
2
s = 92 . 15
----------------
2
s = 1380
------------
2
s = 690
an = -3 + (15-1) . 7
an = -3 + 14 . 7
an = -3 + 98
an = 95
||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||||
s = (a1 + an) . n
----------------------
2
s = (-3 + 95) . 15
-------------------------
2
s = 92 . 15
----------------
2
s = 1380
------------
2
s = 690
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás